Relationship between Knowledge, Attitudes and Practices of BPBD Officers with Optimization of Flood Disaster Management in Makassar City - Femi Marsya Andris; Cahyono Kaelan; Armyn Nurdin (Universitas STRADA Indonesia, 2020)
The research was conducted at the Regional Disaster Management Agency in Makassar City. This type of research is quantitative with analytical survey research methods. The population in this study were all officers of the Regional Disaster Management Agency. The sample of this research is the officers of the Regional Disaster Management Agency in Makassar City, as many as 40 people consisting of 30 office staff and 10 field officers. The results of the research by office staff and field officers showed that knowledge (p value 0.032 <α 0.05), attitude (p value 0.036 <α 0.05), and practice (p value 0.013 <α 0.05). This means that there is a significant relationship between the knowledge, attitudes and practices of Regional Disaster Management Agency officials on optimizing flood disaster management in Makassar City. Knowledge, attitudes and good practices can make all Regional Disaster Management Agency officers more optimal in emergency response to floods